A case for early semester utilization of business simulations. (4th February 2019) - Angolia, Mark; Reed, April Helene
Abstract : Purpose: The purpose of this paper is to encourage the use of simulations early in a semester, rather than as a course capstone activity, in an effort to utilize simulations as a foundational experience. The intent is to support teaching and learning, as opposed to using simulations as a capstone assignment or assessment tool. Design/methodology/approach: A comprehensive literature review synthesizing higher education business simulation effectivity and evaluation methods provides support for the analysis of 60 undergraduate supply chain management students and 96 surveys conducted over two years. The research question explores effectiveness based on the point of time during a semester a simulation was used. Findings: The analysis of simulation effectiveness, based on the impact of course enjoyment and assistance with learning key course competencies, showed no significant differences for simulations used early in a semester or as an end-of-semester capstone event. Practical implications: Simulations are effective tools regardless of when they are employed, but there may be significant benefits to using a simulation early in a semester by capitalizing on the tool's inherent experiential learning functionality, active learning theory and the Kolb Experiential Learning Cycle. Early use of simulations provides common student experiences and creates a foundation for educators to develop a deeper understanding of course concepts. Additional instructor effort is needed to develop external, course specific student work to supplement and enhance the simulation experience. Early use also creates post-simulation debriefing benefits that may be precluded by the end-of-semester simulation events. Originality/value: Evidence suggests that simulations are primarily utilized as course capstone events and/or serve as comprehensive tools to integrate/assess a semester's worth of conceptual learning. This work fills a gap in the research concerning time frames within a semester when simulations are traditionally employed, presenting a paradigm shift toward early utilization.